Avaliação dos benefícios da hidroterapia em recé-nascidos hospitalizados. - Barbosa, Luana Pereira Cunha (2012)
Until decade of 70 , it was believed that newborns do not have pain or pain memory. Last two decades, it has been done an effort to introduce concepts related to humanization and care based on growing. A special attention to pain and to methods that intend to decrease it may be the beginning of better life quality to newborns under neonatal units care. Hydrotherapy has been used as a therapeutic tool for a million years. I has the intention to provide relax, better blood circulation, to repair mobility, to stretch out one s muscles, to rehabilitate, to improve coordination and function, beyond of promoting recreation. This study, almost experimental, had the goal to evaluate the influence of hydrotherapy on hospitalized newborns. The data were obtained on four consecutive months, through a tool of obtained data according to characteristics related to birth, hospitalization and other obtained data: cardiac frequency, respiratory frequency, oxygen saturation, saliva cortisol and Neonatal Infant Pain Scale-NIPS. The population was constituted of all newborns that filled inclusion criteria, totalizing ten newborns. Later, they were submitted to statistic analysis, using measures of central tendency and variability to quantitative changes to inferential analysis for measures to cardiac frequency, respiratory frequency and oxygen saturation, including T-paired test for two groups and analysis of variance with the same measures for three or more groups. The inferential analysis of NIPS and cortisol used signals test and ANOVA-Friedman for three or more groups. It was used Dunn s test for multiple comparisons. The newborns saturation average was 94.3% before hydrotherapy and after the procedure it increased to 97.5%, the cardiac frequency fluctuated from 144.8 hear beats per minute to 129.7 beats per minute, the respiratory frequency varied from 46.8 breathes per minute to 38.9 breathes per minute and the pain scale values stand under three after hydrotherapy, showing that immediately after the procedure, newborns do not feel pain and were more relaxed. Data showed that saliva cortisol levels for evaluation without hydrotherapy, increased on average of 2.9nmol/L at 7:30 minutes to 4.4nmol/L at 8 o clock. After newborns were submitted to hydrotherapy, saliva cortisol levels tended to decrease from 4.5nmol/L to 3.4nmol/L. In conclusion, hydrotherapy may be suggested as a safe method to manage pain in newborn patients, it can be used as an ordinary therapy to minimize acute pain in intensive and semi-intensive therapy newborns units.